2009
DOI: 10.1021/jp9047715
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Study on Short Metal Alkanoates: Lithium Propanoate and Pentanoate

Abstract: Lithium propanoate and pentanoate were characterized by DSC, single crystal and powder XRD and FTIR and impedance spectroscopies. Lithium propanoate presents a solid-to-solid transition (SII-SI) at T(ss) = (549.1 +/- 0.7) K on first heating that varies on the second and next ones, followed by a fusion at T(f) = (606.1 +/- 0.5) K. For lithium pentanoate, two solid-to-solid transitions (SIII-SII and SII-SI), at T(ss) = (205.5 +/- 0.5) K and T(ss) = (325.2 +/- 0.7) K, respectively, and a melting point at T(f) = (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 59 publications
6
40
0
Order By: Relevance
“…However, they are in excellent agreement with values reported for other soaps [27,28]. Other studies [11,[29][30][31] have shown that with increasing temperatures the lamellar structure is maintained, though with increased disorder of the alkyl chains, leading to a reduction in interlayer d spacing. Only on melting is the chain conformation destroyed.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…However, they are in excellent agreement with values reported for other soaps [27,28]. Other studies [11,[29][30][31] have shown that with increasing temperatures the lamellar structure is maintained, though with increased disorder of the alkyl chains, leading to a reduction in interlayer d spacing. Only on melting is the chain conformation destroyed.…”
Section: Resultssupporting
confidence: 89%
“…This indicates that these carbons are in a similar chemical environment. Also, no odd-even alternation was observed in the asymmetric stretch of 1.12 ⁄ LiC 10 1.08 1.07 LiC 11 1.12 ⁄ LiC 12 1.06 1.06 LiC 13 1.10 ⁄ LiC 14 1.05 1.05 LiC 15 1.10 ⁄ LiC 16 1.05 1.04 LiC 17 1.09 ⁄ LiC 18 1.04 1.04 LiC 19 1.08 ⁄ ⁄No available data, q exp ± 0.02 Á 10 3 kg Á m À3 . the methyl groups in the IR spectra [9].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…It presents all the characteristic absorption bands of a valerate by comparison with published data for related compounds like Yvalerate [20], Dy-valerate [19], Li-valerate [21], Zn-valerate [22] and Cu-valerate [18]. The absence of the νs absorption band for H2O around 3400cm -1 [23] indicates that the Ba-valerate produced by the present technique is anhydrous.…”
Section: Resultsmentioning
confidence: 67%